Anterior Chamber Angle Morphometry Measurement Changes to Ambient Illumination Scaling in Visante Time Domain Optical Coherence Tomography. (4th March 2017) - Marion, Kenneth M.; Dastiridou, Anna; Niemeyer, Moritz; Francis, Brian A.; Sadda, Srinivas R.; Chopra, Vikas
ABSTRACT: Purpose : To test the effect of ambient illumination scaling on the reproducibility and reliability anterior chamber metrics using the Visante time domain optical coherence tomography (TD-OCT) instrument. Materials and methods : The inferior irido-corneal angles of 25 normal, healthy eyes were imaged twice with the Zeiss Visante TD-OCT under five strictly controlled ambient light conditions (foot candles (fc) measured with a light meter at camera/eye interface). Each eye was imaged 10 times totaling 250 assessments. Angle opening distance (AOD500/750), trabecular iris space area (TISA500/750), and scleral spur (SS) angle were graded twice by masked, trained graders at the Doheny Imaging Reading Center using the Visante's intrinsic tools. Lighting effects on measurements, intra-/inter-grader and acquisition analyses, and Bland–Altman plots were computed using Statistical Package for Social Science (SPSS Inc. version 18.0, Armonk, NY). Results : With a near linear relationship of angle metrics to lights levels ( R 2 = 0.8–0.95), the analysis examines the differences from the brightest to darkest light levels. Decreasing ambient light levels from 1.0 to 0.0 fc decreased the average AOD500 measurement from 407 ± 136 µm to 315 ± 114 µm (mean percent difference (MPD) 29%, p < 0.001), AOD750 from 587 ± 184 µm to 496 ± 155 µm (MPD 18%, p < 0.001), TISA500 from 136 ± 43 µm 2 to 101 ± 37 µm 2 (MPD 35%, p < 0.001), TISA750 from 269 ± 81 µm 2 to 212 ± 68 µm 2 (MPD 27%, p < 0.001), and SS angle from 38.3% ± 9% to 32.1% ± 9% (MPD 19%, p < 0.001). Intra-/inter-grader results showed good reproducibility for each grader (MPD = 0.7–3%; coefficient of variation (CV) = 3.2–8.3%; R 2 = 0.8–0.95; p < 0.001 for all metrics) and between graders (MPD = 1.4–5.9%; CV = 6.7–14.2%; R 2 = 0.81–0.89; Pearson Correlation Coefficient (PCC) = 0.8–0.97 ( p <0.001)). Bland–Altman plots did not demonstrate any apparent bias, with similar repeatability and agreement. Conclusions : The results of this study show the high sensitivity of the anterior chamber to changes in the illumination. The slight decrease in light had a corresponding large decrease in Anterior Chamber Angle (ACA) metrics. With clinical diagnoses and treatments of eye diseases relying on these angle measurements, these findings emphasize the importance of strictly controlling light conditions in order to obtain reproducible measurements of anterior chamber geometry.